Perceived Weight Discrimination Mediates the Prospective Association Between Obesity and Physiological Dysregulation: Evidence From a Population-Based Cohort. (July 2019) - Daly, Michael; Sutin, Angelina R.; Robinson, Eric
Obesity is thought to cause ill health because of the biological strain that excess fat has on physiological function. We tested an alternative explanation in a population-based sample of 3, 609 older English adults—that the pervasive discrimination experienced by individuals with excess weight may in part explain why obesity is associated with subsequent multisystem physiological dysregulation, measured via clinical indicators of cardiovascular, metabolic, and immune function. We found that both obesity and perceived weight discrimination predicted an increase in physiological dysregulation from baseline to follow-up 4 years later. Perceived discrimination because of body weight experienced by individuals with obesity explained more than one quarter of the prospective association between obesity and a deterioration in biomarkers of health status. These findings highlight the possibility that the stigma experienced by individuals with obesity may play an important role in explaining the obesity-related disease burden.